The Effect of Leadership, Organizational Culture, and Work Motivation on the Performance of Import Goods Physical Inspectors through Job Satisfaction at Medium Customs Type, Customs and Excise Controlling and Servicing Office of Tanjung Perak - Firman Adi Kristanto; Sri Rahayu; Rifda Fitrianty (CV. Era Digital Nusantara, 2026)
This study aims to analyze the effect of leadership, organizational culture, and work motivation on the performance of import goods physical inspectors through job satisfaction at Medium Customs Type, Customs and Excise Controlling and Servicing Office of Tanjung Perak. This study employed a quantitative approach with an explanatory research design. The population consisted of all import goods physical inspectors at Medium Customs Type, Customs and Excise Controlling and Servicing Office of Tanjung Perak, totaling 35 employees. The sampling technique used was saturated sampling, in which the entire population was selected as research respondents. Data were collected through a questionnaire using a 1–5 Likert scale and analyzed using SEM-PLS. The results show that leadership, organizational culture, and work motivation have a positive and significant effect on job satisfaction. Leadership, organizational culture, work motivation, and job satisfaction also have a positive and significant effect on the performance of import goods physical inspectors. In addition, job satisfaction is proven to mediate the effect of leadership, organizational culture, and work motivation on the performance of import goods physical inspectors. These findings indicate that improving the performance of import goods physical inspectors is not only directly determined by leadership, organizational culture, and work motivation, but also through the improvement of job satisfaction. Therefore, the organization needs to strengthen fair and supportive leadership, a disciplined and meticulous work culture, work motivation, and employee job satisfaction.